Energetic consistency of truncated models - ASNANI, G. C. (MAUSAM, 1971)
Energetic consistency of truncated NWP models is examined. It is shown that in this so-called ‘energetically consistent’ model, there are fictitious cancellations of vertical divergences of energy fluxes at each level and hence the vertical coupling of energy in these models is rather defective.